Effect of design features of bogies models 18-4129 and 18-9817 with axle load of 25 tf on dynamic parameters of wagons (Transport systems and technologies, 2019)
The performance of the wagons is directly related to the carrying capacity, which depends primarily on the permissible axial load. In this regard, the choice of the maximum permissible axial load is the most important factor determining the technical and economic characteristics of the wagons being designed. The issue of the permissible axial load has been discussed for many decades. To solve this task, an integrated approach is needed, associated both with improved riding quality of wagons and completion of track preparation and fixed track structures for handling freight trains with axial loads of 25 ton-force.The most innovative are the bogies of models 18-4129 and 18-9817, resulting from the modification of bogie 18-100. Bogie model 18-9817 is a joint development of the American company ASF Keystone and the Ukrainian Industrial and Investment Group InterCarGroup. Bogie design took advantages of structural solutions and technologies used in Motion Control bogie model, which is successfully in service on the railways of the United States and Canada. AdapterPlus adapters with a polymeric gasket are installed in the axlebox of the side frame. The use of this adapter will reduce wheel and rail wear . Bogie model 18-4129 was constructed by Sophia Invest LLC (Ukraine). The frame of the bogie is made of an open structure. Scheffel diagonal braces are used to reduce the lozenging of bogie side frames, reducing the wheel run-up angle on the rails and, consequently, the wear intensity of wheelset flange. Air-spring suspension in a bogie model 18-4129 is a central single-stage with friction wedge-type vibration dampers. The comparative analysis of the study results showed that the dynamic characteristics of the car on bogies 18-4129 and 18-9817 are generally higher than the dynamic parameters of the bogie 18-100; the best values are the coefficient of the vertical body dynamics and unsprung parts of the car in the bogie 18-9817; bogies 18-4129 showed the best value of the coefficient of horizontal dynamics of the body, as well as the frame forces; the acceleration of the car body in the vertical plane is approximately the samefor bogies 18-9817 and 18-4129, and the acceleration in the horizontal plane is less in the bogie 18-4129 with the exception of speeds over 100 km/h; the best value of the stability factor of the wheel against derailment in the loaded mode is for the bogie 18-4129 in the entire range of speeds, and in the empty state for speeds less than 90 km/h.
Keywords: bogie, design, dynamic parameters, speed.